Associations of Pre- and Postnatal Air Pollution Exposures with Child Blood Pressure and Modification by Maternal Nutrition: A Prospective Study in the CANDLE Cohort - Ni, Yu (Environ Health Perspect, 2021)
BACKGROUND: Limited data suggest air pollution exposures may contribute to pediatric high blood pressure (HBP), a known predictor of adult cardiovascular diseases. METHODS: We investigated this association in the Conditions Affecting Neurocognitive Development and Learning in Early Childhood (CANDLE) study, a sociodemographically diverse pregnancy cohort in the southern United States with participants enrolled from 2006 to 2011. We included 822 mother–child dyads with available address histories and a valid child blood pressure measurement at 4–6 y. Systolic (SBP) and diastolic blood pressures (DBP) were converted to age-, sex-, and height-specific percentiles for normal-weight U.S. children. HBP was classified based on SBP or DBP [Formula: see text] percentile. Nitrogen dioxide ([Formula: see text]) and particulate matter [Formula: see text] in aerodynamic diameter ([Formula: see text]) estimates in both pre- and postnatal windows were obtained from annual national models and spatiotemporal models, respectively. We fit multivariate Linear and Poisson regressions and explored multiplicative joint effects with maternal nutrition, child sex, and maternal race using interaction terms. RESULTS: Mean [Formula: see text] and [Formula: see text] in the prenatal period were 10.8 [standard deviation (SD): 0.9] [Formula: see text] and 10.0 (SD: 2.4) ppb, respectively, and 9.9 (SD: 0.6) [Formula: see text] and 8.8 (SD: 1.9) ppb from birth to the 4-y-old birthday. On average, SBP percentile increased by 14.6 (95% CI: 4.6, 24.6), and DBP percentile increased by 8.7 (95% CI: 1.4, 15.9) with each [Formula: see text] increase in second-trimester [Formula: see text]. [Formula: see text] averaged over the prenatal period was only significantly associated with higher DBP percentiles [[Formula: see text] 11.6 (95% CI: 2.9, 20.2)]. Positive associations of second-trimester [Formula: see text] with SBP and DBP percentiles were stronger in children with maternal folate concentrations in the lowest quartile ([Formula: see text] 0.05 and 0.07, respectively) and associations with DBP percentiles were stronger in female children ([Formula: see text] 0.05). We did not detect significant association of [Formula: see text] , road proximity, and postnatal [Formula: see text] with any outcomes. CONCLUSIONS: The findings suggest that higher prenatal [Formula: see text] exposure, particularly in the second trimester, is associated with elevated early childhood blood pressure. This adverse association could be modified by pregnancy folate concentrations. https://doi.org/10.1289/EHP7486